A Rare Case of Large-Vessel Vasculitis following Checkpoint Inhibitor Therapy and Pegfilgrastim. (23rd February 2022) - Mort, Joseph; Maheshwari, Shipra; Basu, Nayanika; Dillon, Patrick; Brady, Kevin; Bear, Harry; Millard, Trish
Abstract : Checkpoint inhibitors (CPIs) and pegfilgrastim, a long-acting growth factor agent, are vital components of current cancer treatments. Immune-related adverse events (irAEs) such as colitis and pneumonitis are well-established toxicities associated with CPI therapy. However, large-vessel vasculitis secondary to CPI utilization is reported only in rare case reports and case series. Interestingly, large-vessel vasculitis has also been reported as a rare complication of pegfilgrastim use. We present a 59-year-old female with left stage IIA (cT2N0M0) triple-negative breast cancer receiving neoadjuvant decitabine and pembrolizumab prior to neoadjuvant chemotherapy (NAC). NAC included standard-of-care dose dense doxorubicin and cyclophosphamide (ddAC) supported with pegfilgrastim use followed by weekly carboplatin and paclitaxel. After receiving her second cycle of ddAC with pegfilgrastim, the patient reported five days of left shoulder and arm pain. Subsequent CT imaging demonstrated wall thickening and inflammatory changes surrounding the left subclavian artery, aortic arch, left carotid artery, proximal innominate arteries, and the mid internal carotid arteries and its branching vessels. These findings were extremely concerning for large-vessel vasculitis. Excluding CPI therapy and pegfilgrastim use, no additional inciting event or medication that the patient was exposed to was noted to be associated with large-vessel vasculitis. We present this case to report on this rare but severe complication from commonly utilized agents in cancer treatment. We also extend the possibility of large-vessel vasculitis development in relation to the COVID-19 vaccine due to shared ingredients found in both the vaccine and pegfilgrastim. It is important to outline the treatment used for such a complication as no standardized treatment has been established for large-vessel vasculitis caused by CPI therapy or pegfilgrastim use.